Is there a proximal-to-distal sequence in overarm throwing in team handball? - van den Tillaar, R.; Ettema, G. (Journal of Sports Sciences, 2009)
Research examining the proximal-to-distal sequencing of segments of the body involved in overarm throwing has been equivocal: some studies have found support for the concept while others have not. The aim of the present study, therefore, was to determine if there is a proximal-to-distal sequence in the timing of the movements of joints and the distal endpoints of segments in overarm throwing. The three-dimensional kinematics of a penalty throw in experienced team handball players (n = 11) were recorded and analysed with regard to the timing of events. We analysed the timing of the maximal velocity of the distal endpoints of six segments and the maximal angular velocity in 11 joints, as well as the initiation of these joint movements. A temporal proximal-to-distal sequence was observed only for the initiation of the joint movements. No such sequence was found for maximal velocity of the joints and distal endpoints of segments.